The relationship between the quality of tertiary education and the levels of socioeconomic conditions in Central Luzon - Bacani, Edna Navarro 1947-
Data about the quality levels of tertiary education and the levels of socioeconomic conditions for 1972 and 1977 were gathered through a questionnaire issued to all the institutions of higher education in the region. Correlation analyses showed such quality level to be low. Socioeconomic levels were high-middle range in 1972, became low-middle in 1977. Additional tests revealed no significant relationships between quality levels of tertiary education and levels of socioeconomic conditions. The quality level among colleges and universities is more associated with internal factors (input resources) of the institutions themselves than with the external factors (socioeconomic indicators) surrounding them.